Towards a common vision of the Church? The Church in the Catholic-Lutheran dialogue - González Montes, Adolfo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
To analyze the situation of the current Catholic-Lutheran dialogue, Malta’s report, The Gospel and the Church (1972), is taken as a basis, in its first, third and fourth points. Thus, we review the diverse understanding of: (1) the primacy of the word of God, with its consequences on Tradition and the Magisterium; (2) the ecclesiastical ministry and its constitutive character for the configuration of the Church; and (3) the apostolicity of the Church and its unity. The ecumenical documents after 1972 are brought up to evaluate both the progress made towards a convergence, and to verify the areas of significant dissent that still continue to separate Catholics and Lutherans from the desired unity.